A medical audit of the management of cryptococcal meningitis in HIV-positive patients in the Cape Winelands (East) district, Western Cape - K.B. von Pressentin; H.H. Conradie; R. Mash (South African Family Practice)
Background: Cryptococcal meningitis (CM) has become the most common type of community-acquired meningitis. CM has a poor outcome if the initial in-hospital treatment does not adhere to standard guidelines. The aim of this audit was to improve the quality of the care of human immunodeficiency virus (HIV) positive patients with CM in the Cape Winelands District.